Application of Cellulose and Paper-Based Products in Building Acoustics - KLIMEK, Aleksandra; ŁATKA, Jerzy F.; NIERADKA, Paweł; DOBRUCKI, Andrzej (Archives of Acoustics, 2024)
This article presents a comprehensive acoustic study of paper-based building products: cellulose wool,paperboard, corrugated cardboard, and honeycomb panels. The material configurations included the intact form as well as the various modifications, i.e., density variation, multiple-layered staking, perforation or acoustic metamaterial setup. Tests covered acoustic absorption and insulation properties, with the last examined under excitation of both a plane wave and a diffused field. Additionally, the cellulose wool is provided with the characteristic impedance and propagation wavenumber results; and the paperboard was tested for its dynamic elastic and damping properties. The paper-based products, giving their weight, prove to be a convincing replacement for conventional materials by both absorptive and insulation performance. The maximum acquired sound reduction index, for exceptionally lightweight (2.2 kg/m^2) paper double-wall metamaterial structure, reached 26 dB.